A lesson from the wild: The natural state of eosinophils is Ly6Ghi. Issue 4 (15th September 2021) - Mair, Iris; Wolfenden, Andrew; Lowe, Ann E.; Bennett, Alex; Muir, Andrew; Smith, Hannah; Fenn, Jonathan; Bradley, Janette E.; Else, Kathryn J.
Abstract: With a long history of promoting pathological inflammation, eosinophils are now emerging as important regulatory cells. Yet, findings from controlled laboratory experiments so far lack translation to animals, including humans, in their natural environment. In order to appreciate the breadth of eosinophil phenotype under non‐laboratory, uncontrolled conditions, we exploit a free‐living population of the model organism Mus musculus domesticus . Eosinophils were present at significantly higher proportions in the spleen and bone marrow of wild mice compared with laboratory mice. Strikingly, the majority of eosinophils of wild mice exhibited a unique Ly6G hi phenotype seldom described in laboratory literature. Ly6G expression correlated with activation status in spleen and bone marrow, but not peritoneal exudate cells, and is therefore likely not an activation marker per se . Intermediate Ly6G expression was transiently induced in a small proportion of eosinophils from C57BL/6 laboratory mice during acute infection with the whipworm Trichuris muris, but not during low‐dose chronic infection, which better represents parasite exposure in the wild. We conclude that the natural state of the eosinophil is not adequately reflected in the standard laboratory mouse, which compromises our attempts to dissect their functional relevance. Our findings emphasize the importance of studying the immune system in its natural context – alongside more mechanistic laboratory experiments – in order to capture the entirety of immune phenotypes and functions. Abstract : Laboratory studies have ascribed eosinophils and eosinophil subsets important roles in tissue development, homeostasis and repair, yet their phenotype and function remain unclear in animals under natural conditions. Wild mice harbour a large pool of Ly6G hi eosinophils, a phenotype rarely reported in laboratory studies and only partially explained by activation status or parasitic infections. Studying house mice in their natural environment can offer insights into environmental factors that have shaped the immune system across evolutionary timescales, complementing more traditional, mechanistic laboratory studies.